Advances in adipose-derived stem cell harvesting: tissue blocks vs. lipoaspirates - Chun Kai Yew; Sadia Farhana; Amirul Ashraf Ahmad Shan Wani; Siti Fatimah Noor Mat Johar; Wan Azman Wan Sulaiman; Nur Azida Mohd Nasir (Journal of Taibah University for Science)
Ensuring a nonenzymatic isolation method for human adipose-derived mesenchymal stem cells (hADSCs) is crucial for safe therapeutic applications. In this study, we introduced an improved mechanical technique to isolate hADSCs from subcutaneous adipose tissue. A total of 382.42 g of adipose tissue was obtained from 19 consented donors, including lipoaspirates (mean: 16.98 g, n = 9) and tissue blocks (mean: 12.11 g, n = 19). Following washing, mincing, and centrifugation, stromal vascular fraction (SVF) cells were collected and subsequently cultured. Notably, the viable SVF yield was 12.47 × 104 cells/ml from tissue blocks and 10.73 × 104 cells/ml from lipoaspirates. Furthermore, at passage 2, hADSCs exhibited typical MSC markers (CD90+/CD73+/CD29+/CD105+/CD34−), while at passage 5, they successfully differentiated into adipocytes, osteoblasts, and chondrocytes. Overall, this method effectively isolates and expands hADSCs without xenogeneic contamination, thereby providing a practical and safe approach for clinical applications.